The representation of Islamic values within Sang Piatu folktale in Kedurang society - Nafisendy, Vieka Tauhidah; Junaidi, Febi; Kusnadi, Asep; Jarudin; Bahri, Saeful; Fikri, Dzul; Pandu; Siregar, Abdurrahman; Junarif, Zafa (Research Journal in Advanced Humanities, 2025)
Folktales contain various life values that society can emulate. Through folktales, readers or listeners can enhance their cognitive abilities and character. The Sang Piatu folktale from the Kedurang offers a range of knowledge and important values to be taught. This research aims to analyze the Islamic values in the folktale of Sang Piatu and the community’s perspective on the existence of this tale in conveying Islamic education. This research is qualitative method. The results of this study indicate that the folktale of Sang Piatu provides Islamic values, namely, morals and etiquette that are very important to be taught to children, such as the obligation to perform prayers, the habit of giving alms, the activity of reciting the Quran, and the habit of maintaining ablution and worshipping at the mosque. Islamic behavior is also demonstrated in the tale of Sang Piatu, such as loving parents, respecting others, and helping one another. From the community’s perspective, the tale of Sang Piatu is conveyed using storytelling techniques accompanied by reviews of the goodness within so children will understand the values contained in the story. This research has a positive impact on shaping the behavior of children to practice Islamic teachings in real life.